The Caenorhabditis elegans LET‐418/Mi2 plays a conserved role in lifespan regulation. Issue 6 (16th August 2013) - De, Véronique; Pfefferli, Catherine; Passannante, Myriam; Belhaj, Khaoula; von, Alina; Sprecher, Simon G.; Müller, Fritz; Wicky, Chantal
Summary The evolutionarily conserved nucleosome‐remodeling protein Mi2 is involved in transcriptional repression during development in various model systems, plays a role in embryonic patterning and germ line development, and participates in DNA repair and cell cycle progression. It is the catalytic subunit of the nucleosome remodeling and histone deacetylase (NuRD) complex, a key determinant of differentiation in mammalian embryonic stem cells. In addition, the Drosophila and C. elegans Mi2 homologs participate in another complex, the MEC complex, which also plays an important developmental role in these organisms. Here we show a new and unexpected feature of the C. elegans Mi2 homolog, LET‐418/Mi2. Lack of LET‐418/Mi2 results in longevity and enhanced stress resistance, a feature that we found to be conserved in Drosophila and in Arabidopsis. The fact that depletion of other components of the NuRD and the MEC complexes did not result in longevity suggests that LET‐418 may regulate lifespan in a different molecular context. Genetic interaction studies suggest that let‐418 could act in the germ‐cell‐loss pathway, downstream of kri‐1 and tcer‐1. On the basis of our data and on previous findings showing a role for let‐418 during development, we propose that LET‐418/Mi2 could be part of a system that drives development and reproduction with concomitant life‐reducing effects later in life.